2023
DOI: 10.18632/aging.204990
|View full text |Cite
|
Sign up to set email alerts
|

Xuebijing injection protects sepsis induced myocardial injury by mediating TLR4/NF-κB/IKKα and JAK2/STAT3 signaling pathways

Xiang-Fei Kang,
Xiao-Li Lu,
Cheng-Fei Bi
et al.

Abstract: Objective: Compelling evidence has demonstrated that Xuebijing (XBJ) exerted protective effects against SIMI. The aims of this study were to investigate whether TLR4/IKKα-mediated NF-κB and JAK2/STAT3 pathways were involved in XBJ's cardio-protection during sepsis and the mechanisms. Methods: In this study, rats were randomly assigned to three groups: Sham group; CLP group; XBJ group. Rats were treated with XBJ or sanitary saline after CLP. Echocardiography, myocardial enzymes and HE were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Improved autophagic flux-based sepsis therapy options are suggested by a clinical investigation that reveals impaired autophagic flux in septic patients [ 173 ]. Our previous basic studies have revealed that activation of autophagy is protective of multiorgan function in a sepsis model [ 174 , 175 ]. Then, cognitive dysfunction in sepsis-related encephalopathy is ameliorated by activation of PPAR-γ signaling pathway-mediated autophagy in astrocytes, as evidenced by high expression of LC3, ULK1, and low expression of P62 [ 176 ].…”
Section: The Regulatory Role Of M 6 a Methylation ...mentioning
confidence: 99%
“…Improved autophagic flux-based sepsis therapy options are suggested by a clinical investigation that reveals impaired autophagic flux in septic patients [ 173 ]. Our previous basic studies have revealed that activation of autophagy is protective of multiorgan function in a sepsis model [ 174 , 175 ]. Then, cognitive dysfunction in sepsis-related encephalopathy is ameliorated by activation of PPAR-γ signaling pathway-mediated autophagy in astrocytes, as evidenced by high expression of LC3, ULK1, and low expression of P62 [ 176 ].…”
Section: The Regulatory Role Of M 6 a Methylation ...mentioning
confidence: 99%
“…Given that IL-6 is an established therapeutic target (Martin et al, 2019;Kang et al, 2020) and Stat3 is an emerging target in managing sepsis (Hui et al, 2009;Hou et al, 2021;Lei et al, 2021), this is important for understanding the working mechanism of ACT001 in sepsis. Coincidentally, a recent publication has shown that XBJ can Frontiers in Pharmacology frontiersin.org improve sepsis-induced myocardial damage and inflammation by regulating the NF-κB and JAK2/STAT3 pathways (Kang et al, 2023). Besides, Stattic ameliorates the cecal ligation and puncture-induced cardiac injury in septic mice via the IL-6-STAT3 signaling pathway (Imbaby and Hattori, 2023).…”
Section: Act001 May Regulate Il-6 Signaling To Relieve Sepsis-induced...mentioning
confidence: 99%
“…Our previous studies have also demonstrated that autophagy and apoptosis play key roles in the occurrence and development of SIMI [7]. The PI3K/AKT/mTOR [8], MAPK [9] and NF-κB [10] and pathways regulate various biological responses, including proliferation, autophagy, inflammation, and apoptosis [11][12][13][14][15]. Inhibition of PI3K/AKT/mTOR signaling pathway can enhance autophagy and thus reduce oxidative stress and apoptosis in LPS -induced sepsis [16].…”
Section: Introductionmentioning
confidence: 96%